Evaluasi Keuangan Perusahaan Industri Pertahanan untuk Mendorong Kemandirian Ekonomi Pertahanan Nasional - Thea Diva; Zainal Abidin; Sri Iswati (Lembaga Kajian Pertahanan Strategis, 2025)
The defense industry has a strategic role in supporting Indonesia's economic independence and national security. Companies such as PT Pindad, PT Dahana, and PT INTI are the main actors in providing defense equipment, explosives, and strategic communication technology. However, financial and operational challenges still hamper their contribution to defense economic independence. This study aims to evaluate the financial performance of the three companies in the 2019-2023 period with a focus on financial performance evaluation analysis. The research method uses a quantitative descriptive approach based on secondary financial data. The results show that PT Pindad and PT Dahana experienced a significant increase in net profit in 2023, amounting to IDR 120.77 billion and IDR 458.46 billion respectively, after facing fluctuations during the study period. In contrast, PT INTI continued to record losses from 2019 to 2023, with the largest loss reaching Rp 434.77 billion in 2019. This finding indicates a significant difference in the company's ability to overcome financial challenges. The implications of this study highlight the importance of strengthening managerial strategies, operational efficiency, and government policy support to sustainably increase the defense industry sector's contribution to national economic independence.